Higher fat stores contribute to persistence of little brown bat populations with white‐nose syndrome. Issue 4 (18th February 2019) - Cheng, Tina L.; Gerson, Alexander; Moore, Marianne S.; Reichard, Jonathan D.; DeSimone, Joely; Willis, Craig K. R.; Frick, Winifred F.; Kilpatrick, Auston Marm
Abstract: The persistence of populations declining from novel stressors depends, in part, on their ability to respond by trait change via evolution or plasticity. White‐nose syndrome (WNS) has caused rapid declines in several North America bat species by disrupting hibernation behaviour, leading to body fat depletion and starvation. However, some populations of Myotis lucifugus now persist with WNS by unknown mechanisms. We examined whether persistence of M. lucifigus with WNS could be explained by increased body fat in early winter, which would allow bats to tolerate the increased energetic costs associated with WNS. We also investigated whether bats were escaping infection or resistant to infection as an alternative mechanism explaining persistence. We measured body fat in early and late winter during initial WNS invasion and 8 years later at six sites where bats are now persisting. We also measured infection prevalence and intensity in persisting populations. Infection prevalence was not significantly lower than observed in declining populations. However, at two sites, infection loads were lower than observed in declining populations. Body fat in early winter was significantly higher in four of the six persisting populations than during WNS invasion. Physiological models of energy use indicated that these higher fat stores could reduce WNS mortality by 58%–70%. These results suggest that differences in fat storage and infection dynamics have reduced the impacts of WNS in many populations. Increases in body fat provide a potential mechanism for management intervention to help conserve bat populations. Abstract : The ability for hosts to rapidly respond to external perturbations (e.g., climate change, habitat destruction, disease) can be critical for long‐term population persistence. This study describes a physiological mechanism in hibernating bats to the disease, white‐nose syndrome. Specifically, increased fat reserves allow bats to tolerate energetic costs of this disease.